Advances in salmonid fish immunology: A review of methods and techniques for lymphoid tissue and peripheral blood leucocyte isolation and application. Issue 95 (December 2019) - Lulijwa, Ronald; Alfaro, Andrea C.; Merien, Fabrice; Meyer, Jill; Young, Tim
Abstract: Evaluating studies over the past almost 40 years, this review outlines the current knowledge and research gaps in the use of isolated leucocytes in salmonid immunology understanding. This contribution focuses on the techniques used to isolate salmonid immune cells and popular immunological assays. The paper also analyses the use of leucocytes to demonstrate immunomodulation following dietary manipulation, exposure to physical and chemical stressors, effects of pathogens and parasites, vaccine design and application strategies assessment. We also present findings on development of fish immune cell lines and their potential uses in aquaculture immunology. The review recovered 114 studies, where discontinuous density gradient centrifugation (DDGC) with Percoll density gradient was the most popular leucocyte isolation method. Fish head kidney (HK) and peripheral blood (PB) were the main sources of leucocytes, from rainbow trout ( Oncorhynchus mykiss ) and Atlantic salmon ( Salmo salar ). Phagocytosis and respiratory burst were the most popular immunological assays. Studies used isolated leucocytes to demonstrate that dietary manipulations enhance fish immunity, while chemical and physical stressors suppress immunity. In addition, parasites, and microbial pathogens depress fish innate immunity and induce pro-inflammatory cytokine gene transcripts production, while vaccines enhance immunity. This review found 10 developed salmonid cell lines, mainly from S. salar and O. mykiss HK tissue, which require fish euthanisation to isolate. In the face of high costs involved with density gradient reagents, the application of hypotonic lysis in conjunction with mico-volume blood methods can potentially reduce research costs, time, and using nonlethal and ethically flexible approaches. Since the targeted literature review for this study retrieved no metabolomics study of leucocytes, indicates that this approach, together with traditional technics and novel flow cytometry could help open new opportunities for in vitro studies in aquaculture immunology and vaccinology. Graphical abstract: Image 1 Highlights: Leucocytes mostly isolated by discontinuous density gradient centrifugation (DDGC). Head kidney (HK) and peripheral blood (PB) were the main sources of leucocytes. Phagocytosis and respiratory burst are the most popular immunological assays. Isolated leucocytes show that dietary manipulations and vaccines enhance immunity. Leucocytes reveal that chemical, physical & pathogenic stressors suppress immunity.